2011
DOI: 10.1111/j.1460-9592.2011.03527.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caudal vs intravenous morphine on early extubation and postoperative analgesic requirements for stage 2 and 3 single‐ventricle palliation: a double blind randomized trial

Abstract: High-dose caudal morphine with bupivacaine delayed the need for rescue morphine analgesia in stage 3 patients. All stage 2 patients required early rescue morphine and had significantly higher postoperative 12-h morphine requirements than stage 3 patients. Early extubation is feasible for the majority of stage 2 and 3 SV patients regardless of analgesic regimen. The study was underpowered to assess differences in extubation failure rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…They concluded that CEM not only delayed the need for rescue analgesia in stage 3 patients but also made early extubation feasible. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that CEM not only delayed the need for rescue analgesia in stage 3 patients but also made early extubation feasible. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized trial of infants undergoing cardiac surgery, caudal morphine and local anesthetic provided some analgesic benefits over systemic morphine, but the study had insufficient power to evaluate effects on early extubation 45 . In case series comparing perioperative neuraxial anesthesia with systemic opioid analgesia, the proportion of neonates requiring postoperative mechanical ventilation was reduced following gastrochisis repair 38 , lung resection for congenital lung lesions 46 , and Nissen fundoplication 47 .…”
Section: Clinical Benefits and Risks Of Neuraxial Analgesiamentioning
confidence: 99%
“…However, the frequent dysphoria and also the QT prolongation, which results from an effect on IKr channels (139,380) and leads to an undefined risk for torsade des pointes led to a FDA mandated "black box warning" (423), which has significantly reduced the use of droperidol both for antiemetic prophylaxis and sedation. The drug still finds use in the developing world and in pediatric cardiac anesthesia in North America because of its immobilizing/sedating effects in young uncooperative children and its lack of respiratory depression per se (672,674).…”
Section: Droperidolmentioning
confidence: 99%